The level of compliance to safety audit in construction industry - Awang, Ahmad Fauzi (2007)
Construction activities have been identified as among the highest activity contributed to the accident at workplace in Malaysia. Safety on the construction site was assessed by the Department of Occupational Safety and Health by conducting safety audits during construction. A standard checklist was used to conduct the audit. This checklist included those items which are compliance to Occupational Safety and Health Act and Factories and Machinery Act and perceived to be important from the safety point of view. These are Occupational Safety and Health management, safety committee, machinery, scaffolding, working at height, public safety, workers quarters, storage facilities, formwork, excavation and shoring, personnel protective equipment, platform, floor opening, edge of open floor, access and egress, electrical safety, cleanliness, health and welfare, piling and demolition. A total of 2038 number of audited have been carried out on construction sites throughout Malaysia by the officers from the Department of Occupational Safety and Health for the years of 2004 and 2005. The data from those audits will be analyzed. The sites will be differentiated into high cost and low cost projects based on the cost of the project that reflected to the requirement of contractor to engaged a safety officer if the project exceeding RM 20.0 millions and highrise and lowrise projects based on the highness of the building. The objectives of this research are to assess the level of safety practiced at various construction projects in Malaysia, to determine the level of compliance to safety audit elements between high cost and low cost projects and between highrise and lowrise constructions. The results of analysis revealed construction sites performed better due to the impact of safety audit carried out at their workplace. In term of category of projects, highrise constructions performed better than lowrise construction. In term of cost of projects, high cost projects performed better than low cost projects simply due to the roles of safety officers engaged by high cost constructions.